Optical properties of Agx Cu1- x I alloy thin films - Krueger, Evgeny; Seifert, Michael; Gottschalch, Volker; Krautscheid, Harald; Schnohr, Claudia S.; Botti, Silvana; Grundmann, Marius; Sturm, Chris (AIP Advances, 2023)
We report on the excitonic transition energy E0 and spin-orbit split-off energy Δ0 of γ-AgxCu1-xI alloy thin films studied by using reflectivity measurements at temperatures between 20 K and 290 K. The observed bowing behavior of the E0 transition as a function of the alloy composition is explained based on first-principles band structure calculations in terms of different physical and chemical contributions within the description of ordered alloys. The spin-orbit coupling is found to increase from a value of 640 meV for CuI to approximately 790 meV for AgI. Furthermore, we show that the temperature-dependent bandgap shift between 20 K and 290 K decreases with increasing Ag-content from 25 meV for CuI to 6 meV for AgI. We attribute this behavior mostly to changes in the contribution of thermal lattice expansion to the bandgap shift.
CRIS-Team Scopus Importer:2023-04-20